(untitled) (Fiep Bulletin - online, 2016)
Feeding practices of children in their first months of life are crucial for the construction of eating habits, and breast milk the essential nourishment for the growth and development of infants up to 6 months. This study aimed to describe the prevalence of mixed breastfeeding in children <4 months attended in Family Health Strategies of the municipality of Macaé - Rio de Janeiro, in 2013. We conducted a descriptive, quantitative study of secondary basis, between January and December 2013, with children <4 months attended in Family Health Strategies. The database from SIAB/SUS – DATASUS were used to collect the following variables: children <4 months exclusive breastfeeding (EBF); children <4 months with mixed breastfeeding (MBF); children <4 months attended in Family Health Strategies; and months of the year. We used the Microsoft Excel 2010 software for data analysis. Data from 3752 children <4 months attended in Family Health Strategies of the municipality of Macaé during the year 2013 were analyzed. In January, the prevalence of EBF and MBF were 73.9% and 24.4%, respectively. In December, the prevalence of EBF and MBF were 87% and 10.7%, respectively. The practice of EBF during 2013 reached near 70%.